ESTUDO CONFORMACIONAL DE CLOROACETAMIDAS EMPREGANDO CÁLCULOS TEÓRICOS E AS ESPECTROSCOPIAS DE RESSONÂNCIA MAGNÉTICA NUCLEAR E INFRAVERMELHO - Santos, Marcela Fonseca (2014)
The study of chloroacetamides has gained economic and technological importance;several researchers have been seeking to improve agricultural practices with the use of herbicides. Thus, the inclusion of computational chemistry to the development of products for the agribusiness might promote great qualitative and quantitative advances in the scientific research. Therefore, interest was raised in studying the conformational analysis of certain chloroacetamides, both in isolated phase and in solution. The objective was to carry out conformational analysis of the chloroacetamides: allidochlor, dichlormid, CDEA, DCCMA, CDCA, pethoxamid, propachlor, acetochlor and dimethenamid, using theoretical calculations and the NMR and IR spectroscopy. The SEP3D theoretical calculations were developed using HF/6-311G. The most stable geometries were stabilized at the level of the theory B3LYP/cc-pVDZ with the program GAUSSIAN 03. PCM calculations were carried out to evaluate the most stable conformations on the polarity of the medium. NBO calculations provided information about the interactions. Infrared and coupled 13C Nuclear Magnetic Resonance spectra were obtained with different solvents. The results revealed agreement when compared to the structures obtained through the theoretical calculation, according to the PCM solvation model. The infrared spectra revealed that the econvoluted carbonyl band related to the conformer with the highest dipole moment value was better favored when the medium polarity increased. Through the 1JCH coupling constants obtained from the 13C coupled NMR spectra, changes occurred in the conformational populations according to the solvent variation. With the aid of MPEs, it was possible to demonstrate, in the more stable conformers, which regions presented higher and lower electronic density, possible action sites.